Dynamite Nashville: unmasking the FBI, the KKK, and the bombers beyond their control - Phillips, Betsy (Third Man Books, 2024)
"Nashville has three unsolved integration-era bombings: Hattie Cotton Elementary School on September 10, 1957, the Jewish Community Center on March 16, 1958, and the home of Civil Rights attorney and Nashville city councilmember, Z. Alexander Looby, on April 19, 1960. Using FBI files, some of which the FBI denied even having, archival materials from all over the Southeast, and interviews with witnesses and a racist bomber, Betsy Phillips attempts to piece together what really happened and why those bombings have never been solved."--Publisher's description